ESTETIKA RESEPSI BAHASA SASAK PARA PEMBAYUN DALAM UPACARA ADAT SORONG SERAH MASYARAKAT SASAK DI PULAU LOMBOK - Nana Rosana; Mahyuni Mahyuni; Burhanudin Burhanudin (Center of Language and Cultural Studies, 2018)
The research was inspired by the beauty of the language used by the speaker called pembayun in the traditional sorong serah ceremony, the bridal application of Sasak people in Lombok. The tradition does happen however, young generations would have neglected the meaning denoted in the languages of the ceremony that contains high values of culture, wisdom and religiously. This study used content analysis and ethnography. Data were collected using observation, interview, documentation, and records. Informants that were the native speakers of Sasak and Sumbawa and have the authority on the traditional ceremony were selected. The results show: (1) aesthetically, the form of language used in the reception is the highest form in the Sasak language, which not all Sasak people are able to understand and use; (2) the aesthetic function of the reception of the swinging language in the sorong serah event is a means to convey the message, religion, custom and morals; and (3) the aesthetic value contained in the pembayun language refer to very high moral values and needs to be known by the public at large.